Nanoparticle migration on the microchannel wall surface in low-Reynolds-number nanofluids - Seongjun Ko; Junho Lee; Jiwon Yu; Debjyoti Banerjee; Seok-Won Kang (AIP Advances, 2024)
In this study, nanoparticle deposition probabilities were numerically estimated for aqueous TiO2–water nanofluid flows (containing a colloidal suspension of TiO2 nanoparticles with a nominal diameter of 50 nm) in a microchannel under constant heat flux boundary conditions. To determine the effect of different thermo-hydraulic conditions on the nanoparticle migration near the wall surface at very low Reynolds numbers (i.e., ∼5), a user-defined function code for nanoscale interactions between molecules was considered in addition to the Euler–Lagrange model based on conventional computational fluid dynamics and heat transfer methods. The simulation results were compared with experimental observations to assess the accuracy of the numerical model. Furthermore, the effects of various parameters, such as the flow rate, wall temperature, and particle concentration, on the deposition probability of nanofluids were studied. The dominant factors enhancing the deposition probability were as follows: nanoparticle fraction (1.64) > flow rate (1.30) > heat flux (1.0).